Research into the process of duplicating straw cap details - Арабулі, А. Т.; Грима, А. Р. (Fashion Industry, 2026)
Purpose. Ensuring the quality of the process of duplicating materials from straw on industrial equipment and establishing the influence of temperature and time factors on the duplicating process. Methodology. When conducting the study, methods of mathematical experimental planning and statistical processing of experimental results, mathematical modeling of the processes of forming and shape-fixing of headdress parts made of straw materials were used. Results. When duplicating the details of a headdress made of straw materials, in order to soften them, it is necessary to moisten them, except for the details of the lining, which allows you to give and fix the shape of the product. The optimal parameters of the duplicating process have been established, which are determined by the temperature T=1300C, duplicating time t=30s and which ensure a high level of product processing quality while minimizing energy costs. Scientific novelty. It consists in establishing the optimal parameters of the process of duplicating parts of a hat made of straw materials, which ensures a normalized level of process quality and establishing the influence of the temperature parameter on the duplicating process, rather than the duplicating time. Practical value. The results obtained are the basis for duplicating straw parts and ensuring a high level of quality of the operation, as well as when designing the selection of adhesive gasket materials.